A fixed point approach to approximate quadratic functional equation in non-Archimedean L*-fuzzy normed spaces - 박춘길 (JOURNAL OF INTELLIGENT & FUZZY SYSTEMS, 2020)
We establish some stability results concerning the 2-dimensional vector variable quadratic functional equation f(x + y, z + w) + f(x - y, z - w) = 2f(x, z) + 2f(y, w) in non-Archimedean L*-fuzzy normed spaces.
Keywords: L*-fuzzy metric and normed space; Hyers-Ulam stability; quadratic functional equation; non-Archimedean L*-fuzzy normed space